1994
DOI: 10.1002/cne.903500309
|View full text |Cite
|
Sign up to set email alerts
|

Plasticin, a newly identified neurofilament protein, is preferentially expressed in young retinal ganglion cells of adult goldfish

Abstract: The adult goldfish retina and optic nerve display continuous growth, plasticity, and the capacity to regenerate throughout the animal's life. The intermediate filament proteins in this pathway are different from those in adult mammalian nerves, which do not continuously grow or normally regenerate. One novel intermediate filament protein of the goldfish visual pathway is plasticin, which is synthesized in ganglion cells and transported into the optic nerve. Using specific polyclonal antibodies raised against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…2B, lane 2). These results expand the observations of Fuchs et al (1994), who showed that plasticin antibody recognizes two goldfish proteins that differ slightly in their molecular weights. In zebrafish, Asch et al (1998) isolated two plasticin cDNAs with predicted molecular weights of 51.4 kDa and 52.6 kDa.…”
Section: Goldfish Plasticin Antibody Recognizes Two Variants Of Zebrasupporting
confidence: 89%
See 4 more Smart Citations
“…2B, lane 2). These results expand the observations of Fuchs et al (1994), who showed that plasticin antibody recognizes two goldfish proteins that differ slightly in their molecular weights. In zebrafish, Asch et al (1998) isolated two plasticin cDNAs with predicted molecular weights of 51.4 kDa and 52.6 kDa.…”
Section: Goldfish Plasticin Antibody Recognizes Two Variants Of Zebrasupporting
confidence: 89%
“…In contrast, developmental expression of the nIF peripherin is confined to distinct PNS neurons and CNS neurons that project axons toward the periphery (Parysek et al, 1988;Escurat et al, 1990;Gorham et al, 1990;Troy et al, 1990a). These progressive changes in nIF protein expression fulfill the varying requirements for plasticity and stability in growing axons (Glasgow et al, 1992(Glasgow et al, , 1994aNixon and Shea, 1992;Fuchs et al, 1994;Giordano et al, 1995;Zhao and Szaro, 1997b).…”
mentioning
confidence: 82%
See 3 more Smart Citations